Optimization and Security Analysis of Interconnected Security Control Based on Semantic of Process Communication - Bo LU; Yueming LU (天地一体化信息网络)
Facing the demand of multi-domain security control in the integrated network of air and ground, to solve the problem that singleprocess regular matching restricts the performance of interconnected security gateway, the method of high-performance optimization of interconnected security control based on semantic security analysis of process communication was proposed.The interaction model of master-slave processes was described in a parallel programming language in the method.The state transition system semantics were given to accurately express the combined semantics of the master-slave processes.The security of master-slave processes in combinatorial semantics was analyzed, which ensured that the parallel running of processes had no deadlock and starvation, and was equivalent to the original regular matching.Experimental results showed that the proposed method could give full play to the advantages of multi-core hardware and reduced the context switching overhead of the scheduler.In the case of complex regular expressions, the method was an order of magnitude better than single-core running.